Dystocia due to accumulation of fluid in peritoneal cavity and intestines of fetus in a cross bred cow - HONPARKHE, M; KUMAR, AJEET; GANDOTRA, V K (The Indian Journal of Animal Reproduction, 2003)
A rare case of dystocia due to accumulation of fluid both in fetal intestines and peritoneal cavityin a cross- bred cow was treated with obstetrical manoeuvres.
Keywords: Dystocia; fetal dropsy; fetal ascites